The feasibility and effectiveness of universal antiretroviral therapy provision in adults: The Treat-All approach in the public-sector in rural Swaziland - Kerschberger, Bernhard (Department of Public Health and Family Medicine, 2022)
The World Health Organization (WHO) recommends antiretroviral therapy (ART) initiation at the time of HIV diagnosis irrespective of immunological criteria – known as Treat-All – aiming at improving individual level health outcomes and reducing HIV transmission. However, concerns were raised about the feasibility of further treatment expansion in already fragile health systems in resource-limited settings (RLS). This thesis evaluates the feasibility of ART expansion under the Treat-All approach in a public sector setting in Eswatini. A wide range of HIV care expansion outcomes were explored at patient, programme, and population level. The studies were conducted in outpatient departments of primary and secondary care facilities of the predominantly rural Shiselweni region of Eswatini, from 2007 to 2016. The study population consisted of people living with HIV (PLHIV) who were offered ART under Treat-All and standard of care (SOC) as well as HIV co-infected tuberculosis (TB) patients. The result section of this thesis presents the findings through submitted and published manuscripts. The first paper describes the feasibility of rapid public sector ART expansion before the Treat-All approach became policy. The active ART cohort and treatment coverage among PLHIV expanded approximately 8-fold. Attrition decreased over time, which was most pronounced in the most recent treatment cohort. Attrition remained high for previously described higher risk socio-demographic (e.g. young age, men), clinical (e.g. higher WHO clinical stage, lower CD4 cell count), and programme factors (e.g. toxic drug regimens). The second paper investigates the feasibility of ART initiation under Treat-All compared with SOC. ART initiation was higher and quicker under Treat-All, mainly because more patients with high baseline CD4 cell count initiated treatment under the policy of universal ART. ART initiation was delayed for patients co-infected with TB disease under Treat-All, but was higher overall after 1 month compared with patients without TB. Patients presenting with advanced HIV disease (CD4 < 200 cells/mm3 and/or WHO III/IV clinical stage) had similar cumulative ART initiation rates with both interventions, although initiation was faster under Treat-All during the first month after care enrolment. The third paper assesses treatment outcomes of patients initiated on ART under Treat-All compared with SOC. Patients under Treat-All initiated ART with a higher median CD4 cell count and were more likely to achieve viral suppression. The risk of an unfavourable treatment outcome and viral failure was similar between both interventions. Under Treat-All, previously described higher risk socio-demographic (e.g. younger age, pregnancy) and clinical factors (e.g. low CD4 cell count, higher WHO clinical staging) increased the risk of the unfavourable outcome. The fourth paper evaluated the effectiveness and efficacy of ART initiation on the day of facility-based HIV care enrolment under Treat-All compared with patients initiated 1 to 14 days after care enrolment. Among patients initiated on treatment, same-day ART initiation increased the risk of an unfavourable outcome. This effect was mainly seen during the first months of ART after HIV care enrolment. The fifth paper describes temporal trends in HIV-associated TB during rapid ART expansion including the time-period of Treat-All. Notifications of TB disease decreased by 5-fold over a period of 8 years, and the decline was most pronounced in HIV-associated TB disease compared with HIV-negative TB. The main population-level predictor of TB disease was HIV disease, and the decline in TB coincided with increased access to ART in PLHIV. The thesis concludes that ART expansion and Treat-All are feasible in this RLS, by achieving favourable HIV care outcomes in terms of ART initiation and treatment, for patients with high CD4 cell counts as well for patients presenting late to HIV care. It also highlights the potential population level impact of rapid ART expansion on reducing the burden of HIV-associated TB disease over time. It cautions however against the assumption that outcomes will be improved through ART initiation on the same day as facility-based HIV care enrolment under the Treat-All approach.